How Thomas Hardy Unfolds His Tragic Consciousness Technically in Tess of the D’Urbervilles - Zhang, Jianjun; Zhao, Xiuqin (International Journal of English Literature and Social Sciences (IJELS), 2019)
Abstract: Tess of the D'Urbervilles is one of Thomas Hardy's most famous tragic novels, in which he gives a vivid description of a tragic story about a very pretty rural girl who is seduced by one man , deserted by the other and convicted to be hanged for stabbing the former in order to get the true love from the latter. Thomas Hardy is very good at looking at life in a tragic way and describing the human suffering in the tragic sentiment and a unique manner. In the novel, Thomas Hardy tries his ways to unfold his tragic consciousness thematically and technically so as to make the readers sense and share it throughout the the whole book. In this paper, I will explore how he employs the perfect structure of the novel and other writing techniques to exaggerate the atmosphere of tragedy, profoundly portray the personality of the characters and their inner world, intensify the writer's tragic consciousness and sharply criticize the hypocrisy of the morality and religion in the capitalist society.